Pengaruh Harga Dan Kualitas Produk Terhadap Kepuasan Konsumen Helm INK Di Jakarta - Nursalim, Mochammad Fadli; Juardi, Juardi (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Consumer satisfaction is one of the important factors that companies need to pay attention to so that a business can run for a long time. Because with satisfaction, consumers will continue to buy the products and services offered. This research aims to analyze the influence of price and product quality, both partially and simultaneously, on consumer satisfaction with INK helmets in Jakarta. Using a descriptive quantitative approach, the number of samples in this study was 70 people taken using purposive sampling techniques. Data were analyzed through multiple regression analysis, t test, F test and coefficient of determination test. The results of the research show that product price has a positive and significant effect on consumer satisfaction as shown by the calculated t value (2.449) > t table (1.683), product quality has a positive and significant effect on consumer satisfaction as shown by the calculated t value (2.582) > t table (1.683) and simultaneously the two independent variables have a positive and significant effect on employee performance as shown by the calculated F value (4.611) > F table (3.23). The magnitude of the influence of product price is 75.6%, product quality 77.7% and together 88.6%.